Realization of Appraisal and Ideology in Ferdy Sambo Case in Editorial Text of "Kasus Sambo Isih Dawa" and "Ganjaran Murwat Tumrap Kejujuran" in Panjebar Semangat Magazine - Risdianto, Faizal; Nugroho, Haryo Aji; Sunardi, Sunardi; Arkida, Teisar (Indonesian Journal of EFL and Linguistics, 2024)
This research aims to identify appraisal devices in two editorial texts in the Javanese magazine Panjebar Semangat on the news texts of Ferdy Sambo case entitled Kasus Sambo Isih Dawa and Ganjaran Murwat Tumrap Kejujuran and describe the ideology of the author of the editorial text. Data were analyzed using the Appraisal System in Functional Systemic Linguistics, including Attitude, Graduation, and Engagement. The results of the appraisal analysis on the first text are 69 attitudes data from 68 clauses. A total of 69 attitudes data were found, consisting of 33 positive attitudes and 36 negative attitudes. Monogloss data with 44 data dominate these attitudes compared to heterogloss data with 25 data. In terms of Graduation, journalists used the intensifier type only eight times. For the second text, 55 attitudes data from 48 clauses. The total of 55 data was dominated by positive evaluations of 43 data, while there were only 12 negative evaluations. It can be interpreted that this editorial text has a very positive nuance. The text is dominated by monogloss data, namely 47 data, compared to heterogloss data, which is only 8 data. The outcomes of the analysis conducted on the editorial texts within the Panjebar Semangat Javanese magazine indicate a predominant reliance on judgment as the principal method of Appraisal, succeeded by appreciation and affect. The analysis explicitly emphasizes the assessment of individual character traits, with Richard, Sambo, and Putri identified as the primary subjects of evaluation. This finding underscores the potential of news as a mechanism for the exercise of social control, with the deployment of judgment serving to consolidate specific societal values and beliefs. This editorial text makes journalists themselves the dominant source of evaluators. In terms of Graduation, journalists also tend to increase their Attitude appraisal using intensifiers. The dominance of monogloss in the editorial text is linguistic evidence that the journalist deliberately composed the editorial text using the point of view of himself.